The Existence of Provincial Regulations and Special Regional Regulations as Legal Products in Fulfilling Education Access for the Community in Papua - Lily Bauw (Journal of Law, Politic and Humanities, 2024)
Education is a basic right of every human being that must be fulfilled by the state. Apart from being a basic right, education is also a basic aspect in ensuring the survival of the nation and state. The aim of this research is to determine the synchronization, both vertically and horizontally, of the existence of Perdasi Number 2 of 2013 and Perdasi Number 3 of 2013 and to determine the effectiveness (effectiveness) of implementing Perdasi Number 2 of 2013 and Perdasi Number 3 of 2013 in the community. The approach used in this research is a normative juridical approach, normative juridical is intended to examine problems related to Perdasi Number 2 of 2013, and Perdasi Number 3 of 2013, using document studies of statutory regulations and sharing policies related to the main issues related matters and reports on the results of various meetings including Focus Group Discussions (FGD). The results of this research reveal that the Provincial and Regency Governments provide the widest possible opportunities to religious institutions, non-governmental organizations and the business world that meet the requirements in accordance with statutory provisions to develop and provide quality education. To support the continuity of the implementation of education services provided by the community, the provincial and district governments are required to provide assistance and/or subsidies to the organizers. Provincial, Regency/City Governments have waived and reduced educational costs, especially for OAP, in the form of giving cash to students who are received every third of the month, as well as providing domestic and international scholarships, but this funding has not had a significant effect in increasing the quality of students, due to the absence of supervision/assistance from the local government, or supervision carried out but not optimally, so that there are students or students who fail in pursuing their education.